2020
DOI: 10.1186/s12933-019-0979-x
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone and PPAR-γ modulating treatment in hypertensive and type 2 diabetic patients after ischemic stroke: a national cohort study

Abstract: Background and aim: Peroxisome proliferator-activated receptor-γ (PPAR-γ) modulating treatment may have cardiovascular benefits in type 2 diabetes mellitus (T2DM) patients after ischemic stroke (IS). However, whether there are additional benefits from intensive PPAR-γ modulating treatments in Asian patients with T2DM and hypertension (HTN) after IS remains unknown.Methods: Between 2001 and 2013, patients admitted due to IS were identified from the National Health Insurance Research Database of Taiwan. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Data from these studies provide strong evidence to support the use of pioglitazone for secondary stroke prevention, and it is possible that the results could be extended in the future to populations without a history of stroke [13]. Based on real-world data, the effect of pioglitazone on stroke varies according to the different clinical characteristics of patients and the interaction with other glucose-lowering agents [14][15][16][17][18]. A meta-analysis of randomized-controlled trials (RCTs) revealed that pioglitazone reduced the risk of stroke in patients with a history of established cardiovascular (CV) diseases [19].…”
Section: Introductionmentioning
confidence: 97%
“…Data from these studies provide strong evidence to support the use of pioglitazone for secondary stroke prevention, and it is possible that the results could be extended in the future to populations without a history of stroke [13]. Based on real-world data, the effect of pioglitazone on stroke varies according to the different clinical characteristics of patients and the interaction with other glucose-lowering agents [14][15][16][17][18]. A meta-analysis of randomized-controlled trials (RCTs) revealed that pioglitazone reduced the risk of stroke in patients with a history of established cardiovascular (CV) diseases [19].…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, blood glucose could be controlled but the endogenous secretion of insulin has not been increased yet [ 5 ]. Studies have shown that pioglitazone might reduce major adverse cardiovascular events, correct multiple components of metabolic syndrome, and improve nonalcoholic fatty liver disease [ 6 , 7 ]. However, side effects such as weight gain, fluid retention, or even fracture could not be ignored either [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A national cohort study showed that Asian patients with ischemic stroke taking pioglitazone for type 2 diabetes mellitus (T2DM) could lower the risks of recurrent ischemic stroke during the long term follow-up. And their data provided the evidence of pioglitazone for secondary prevention of ischemic stroke in Asian T2DM patients, which provides a theoretical basis for the development of new cardiovascular and cerebrovascular disease drugs (9). The research progress of PPARγ agonists in the treatment of CI/RI in the last 5 years is summarized in the Table 1 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%